2001
DOI: 10.1046/j.1440-6047.2001.00245.x
|View full text |Cite
|
Sign up to set email alerts
|

Self‐rated health and its relationship to functional status and well‐being in a group of elderly Guatemalan subjects

Abstract: This study examined the association of self-rated health with physical function and emotional well-being, while controlling for differences in sex, age and anthropometry. Subjects were participants in a multicentre study originated by the International Union of Nutritional Sciences (IUNS). A total of 151 elderly Guatemalan subjects were examined using a questionnaire which included information on self-rated health, activities of daily living, well-being, and a common battery of anthropometric variables. Adjust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…In this nationally representative sample of community‐dwelling people aged 70 and older, global perceived health status, types of physical and mental conditions, and perceptions of home environmental barriers were all associated with ADL stage in complex ways, consistent with the HEI 13 framework. Concordance with other studies and clinical plausibility of the relationships support the internal validity of the stages 20,24,30–34 . An enhanced understanding of associations between ADL stage and other health‐related concepts has the potential to improve the care of populations and persons with disabilities in several ways.…”
Section: Discussionsupporting
confidence: 55%
“…In this nationally representative sample of community‐dwelling people aged 70 and older, global perceived health status, types of physical and mental conditions, and perceptions of home environmental barriers were all associated with ADL stage in complex ways, consistent with the HEI 13 framework. Concordance with other studies and clinical plausibility of the relationships support the internal validity of the stages 20,24,30–34 . An enhanced understanding of associations between ADL stage and other health‐related concepts has the potential to improve the care of populations and persons with disabilities in several ways.…”
Section: Discussionsupporting
confidence: 55%
“…DeSalvo et al (2005) conducted a review of 22 cohort studies and found that a single-item, self-rated question was strongly associated with mortality and could be used to represent general wellness. Other studies showed that the participants with higher scores on the well-being index were more likely to rate themselves in "good" health in the one-item scale (Herman et al, 2001) and a single question for SRH was significantly related to functional health in primary care (Rohrer et al, 2007). A single-item, five-point Likert scale was adopted in this study.…”
Section: Instrumentsmentioning
confidence: 99%
“…Self-rated health status represents one's self-report regarding general personal health status. Although subjective, it is a valuable indicator of health evaluation in practice 8 . It not only represents the current and long-term health status, but also predicts illness and disability in the future 9 .…”
Section: Introductionmentioning
confidence: 99%